(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
At the Fine Arts Museum of Budapest there are six Corinthian Capitals bought by Károly Pulszky in Italy in 1985. They were published in 1955 by Ákos Kiss who believed they came from Brescia. This paper aims to reanalyze the six Capitals to verify the chronology and the origin through comparisons and a bibliographic update. Thanks to the petrographic analysis conducted by Roberto Bugini, it has been possible to identify the stone and an autoptic analysis has allowed to identify and to study the design framework signs.